2019
DOI: 10.15171/ijep.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Staphylococcal Cassette Chromosome mec and Panton-Valentine Leukocidin Gene Amongst the Methicillin-resistant Staphylococcus aureus Strains Isolated From Fowl Meat

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is considered to be one of the most important causes of foodborne diseases. Objective: The current examination was performed to examine the distribution of staphylococcal cassette chromosome mec (SCCmec) and Panton-Valentine leukocidin (PVL) gene amongst the MRSA strains isolated from raw fowl meat samples. Materials and Methods: A total of 240 fowl meat samples were collected and cultured. MRSA strains were identified using cefoxitin and oxacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As far as we know, no other study has reported the prevalence and carriage of MRSA in quails at the slaughterhouse level. Very few studies have been carried out so far in quails, and they report the presence of MRSA strains in quail eggshells or meat [36][37][38]. Saadati et al (2019) sampled meat from 70 quails randomly collected from the shopping centers in Iran and found only two (2.86%) MRSA strains [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, no other study has reported the prevalence and carriage of MRSA in quails at the slaughterhouse level. Very few studies have been carried out so far in quails, and they report the presence of MRSA strains in quail eggshells or meat [36][37][38]. Saadati et al (2019) sampled meat from 70 quails randomly collected from the shopping centers in Iran and found only two (2.86%) MRSA strains [38].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been carried out so far in quails, and they report the presence of MRSA strains in quail eggshells or meat [36][37][38]. Saadati et al (2019) sampled meat from 70 quails randomly collected from the shopping centers in Iran and found only two (2.86%) MRSA strains [38]. Poultry, and poultry meat in general, seem to frequently carry MRSA strains.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the presence of MRSA in raw and frozen chicken meat in different countries worldwide, such as China [20], Bangladesh [89,90], Hong Kong [22], and Egypt [21,91]. Interestingly, MRSA strains were also isolated from quail meat [92][93][94]. Recently, Saadati et al [95] found that 2 of 70 (2.86%) quail samples were MRSA strains in shopping centers of Iran.…”
Section: Poultry Productsmentioning
confidence: 99%